Competitiveness of Indonesia’s Paper in Japan’s Market - Atasha, Maya; Simangunsong, Bintang Charles Hamonangan; Manurung, Elisa Ganda Togu (Department of Forestry, Faculty of Agriculture, University of Lampung, 2025)
Paper and paperboard consistently contribute to Indonesia’s foreign exchange reserves with high export values. Research on demand and other economic analyses related to paper and paperboard products in Indonesia is insufficient. This paper focuses on Indonesian paper and paperboard competitiveness in international markets, especially in strengthening the Indonesian economy and supporting sustainable growth. Paper with Harmonized System Code 480256 is the largest proportion of Indonesia’s exported paper and is mostly exported to Japan. The import share of Indonesian paper in Japan’s market was approximately 69% from 2010 to 2023. Based on the Quadratic Almost Ideal Demand System (QUAIDS) model, the import demand of Indonesian paper was found to be elastic. Moreover, China and Indonesia papers were substitutes, whereas Indonesia and the United States papers were complementary. Expenditure elasticity analysis further showed that Indonesia’s paper was a normal good in Japan’s market. These results highlight the policy relevance for policymakers in designing and improving Indonesia’s forest products for international trade. Keywords: budget share, export, paper, price elasticity, QUAIDS